2009
DOI: 10.1096/fj.08-124420
|View full text |Cite
|
Sign up to set email alerts
|

Pericentrin, a centrosomal protein related to microcephalic primordial dwarfism, is required for olfactory cilia assembly in mice

Abstract: The Drosophila pericentrin-like protein has been shown to be essential for the formation of the sensory cilia of chemosensory and mechanosensory neurons by mutant analysis in flies, while the in vivo function of pericentrin, a well-studied mammalian centrosomal protein related to microcephalic primordial dwarfism, has been unclear. To determine whether pericentrin is required for ciliogenesis in mammals, we generated and analyzed mice with a hypomorphic mutation of Pcnt encoding the mouse pericentrin. Immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 39 publications
(49 reference statements)
7
41
0
Order By: Relevance
“…This is in accordance with our observations in primary DRG cultures (Supporting Fig. S-5) and previous reports in different cell types 25,27,41,46 . We did not observe any difference in Pcnt expression between Piezo2-GFP-positive (41.5 ± 0.06% of DRG were Piezo2-GFP-positive) and -negative neurons, respectively (Fig.…”
Section: Characterization Of Pcnt Expression In Murine Somatosensory supporting
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with our observations in primary DRG cultures (Supporting Fig. S-5) and previous reports in different cell types 25,27,41,46 . We did not observe any difference in Pcnt expression between Piezo2-GFP-positive (41.5 ± 0.06% of DRG were Piezo2-GFP-positive) and -negative neurons, respectively (Fig.…”
Section: Characterization Of Pcnt Expression In Murine Somatosensory supporting
confidence: 94%
“…To this end we employed two different antibodies, which were extensively used in previous studies to visualize Pcnt [24][25][26][27][28][29] . In total agreement with these studies in different cell types both antibodies showed Pcnt expression at centrosomes and in puncta throughout the cytoplasm (Supporting Fig.…”
Section: Characterization Of Pcnt Expression In Murine Somatosensory mentioning
confidence: 99%
“…4 Notably, ciliary abnormalities arose in the d-plp mutant flies, a phenotype reflected in the recent description of defective olfactory cilia formation in mice with a gene trap insertion in the 5' untranslated region of the first exon of Pcnt. 21 Together, these data clearly implicate pericentrin in regulatory and signaling functions of the centrosome. Loss-of-function mutations in PCNT have been described in microcephalic osteodysplastic primordial dwarfism type II (MOPD II; MIM 210720), a rare condition that is characterized by extremely short stature and microcephaly, but without marked mental retardation.…”
Section: Knockdown or Expression Of Dominant-negative Pericentrinmentioning
confidence: 84%
“…Patients have primordial dwarfism, microcephaly, and developmental abnormalities in the ear and patella (Klingseisen and Jackson 2011). Other developmental disorders that cause primordial dwarfism and microcephaly, including Seckel syndrome, have mutations in the centrosome proteins CPAP (CENP-J), PCNT, and CEP152, although defects in a few noncentrosome proteins such as ATM and IGF1 are also associated with microcephalic primordial dwarfism (Rauch et al 2008;Miyoshi et al 2009; Thornton and Woods 2009;Kitagawa et al 2011;Klingseisen and Jackson 2011;Sir et al 2011;Tang et al 2011). A survey of the mutations and phenotypes in 45 Meier-Gorlin syndrome patients demonstrated that compared with patients with mutations in Orc4, Cdc6, and Cdt1, all of the patients with mutations in Orc1 were of significantly shorter stature and had increased microcephaly and a significantly proportionally smaller head circumference and brain (de Munnik et al 2012).…”
mentioning
confidence: 99%